Single-Nanometer-Sized Low-Valence Metal Hydroxide Crystals: Synthesis via Epoxide-Mediated Alkalinization and Assembly toward Functional Mesoporous Materials - Tarutani, Naoki; Tokudome, Yasuaki; Jobbagy, Matias; Viva, Federico Andrés; Soler Illia, Galo Juan de Avila Arturo; Takahashi, Masahide (American Chemical Society, 2016)
Fil: Tarutani, Naoki. Osaka Prefecture University; Japón